Implementation of Innovation Development Means for the Economical Expansion of Enterprises - Miečinskas, Aldas (Ekonomika, 2001)
Making more active of innovations in enterprises is a perspective economical development possibility for transformed or developing countries to expend their economy. In this article stirring up of innovations is represented as social and economic process, which includes all members of the society in the country. Furthermore the possibilities of innovations making more active in the enterprises are analysed, classified and evaluated.